2014
DOI: 10.1055/s-0034-1376963
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Anxiolytic Effects of the Methanol Root Extract of Capparis thonningii: Involvement of Monoaminergic, Cholinergic and GABAergic Systems

Abstract: The findings from this study suggest antidepressant-like effect of C. thonningii involving interaction with serotonergic (5-HT2), dopaminergic (D2), noradrenergic (α1 and α2), and muscarinic cholinergic systems; and anxiolytic effect through an interaction with GABAA benzodiazepine receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…External symptoms were estimated through hole cross checks to complete the approval of anxiousness. Some studies have found that plant extracts rich in alkaloids, glycosides, and flavonoids have sedative, anxiolytic, and antiepileptic properties that interfere with their properties at the benzodiazepine site of the GABAergic complex structure or are immediate or aberrant modulators that are responsible for increases in GABA activity in the brain that cause drowsiness and facies [ 33 , 34 ]. It seems that the phytochemicals included in the extract of Polyalthia suberosa leaves contribute to the relaxing and sleep-inducing actions on the CNS, at least to a limited degree.…”
Section: Discussionmentioning
confidence: 99%
“…External symptoms were estimated through hole cross checks to complete the approval of anxiousness. Some studies have found that plant extracts rich in alkaloids, glycosides, and flavonoids have sedative, anxiolytic, and antiepileptic properties that interfere with their properties at the benzodiazepine site of the GABAergic complex structure or are immediate or aberrant modulators that are responsible for increases in GABA activity in the brain that cause drowsiness and facies [ 33 , 34 ]. It seems that the phytochemicals included in the extract of Polyalthia suberosa leaves contribute to the relaxing and sleep-inducing actions on the CNS, at least to a limited degree.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made in other studies. 73 , 76 Moreover, reports are available showing that the antidepressant-like activity of some isolated flavonoids is abolished by atropine, suggesting the involvement of the cholinergic system in their action. 77…”
Section: Discussionmentioning
confidence: 99%
“…71,72 Pretreatment with sulpiride significantly reversed the antidepressant-like activity of CSE, suggesting that the effect may also be related to the dopaminergic system. Indeed, several studies have suggested the role of sulpiride in altering the antidepressant-like activity of various plant extracts in rodents 66,73 as well as the influence of some flavonoids on the dopaminergic system. 74,75 The cholinergic system plays an important role in the regulation of central functions such as arousal, attention, cognition, and memory.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Species such as Eysenhardtia polystachya (Ortega) Sarg. (Leguminosae) [386], Capparis brassii DC (syn: Capparis thonningii Schumach., Capparaceae) [387], and Cnestis ferruginea Vahl ex DC (Connaraceae) [388] could also be of interest for antidepressant studies.…”
Section: Dosementioning
confidence: 99%